A nasalidade no dialeto quilombola do Norte de Minas: uma análise contrastiva baseada em corpus - Silva, Wagner Cassiano da (2016)
This research investigated the nasality of vowels in the spontaneous speech of inhabitants of the quilombola communities of Brejo dos Crioulos and Poções (MG). As a theoretical framework, we based on the assumptions of Phonetics and Phonology, in renowned scholars on the investigation of nasality (CAGLIARI, 1977; CÂMARA JR., 1984, 2013; BISOL, 2013; ABAURRE; PAGOTTO, 1996; SILVA, 2015), with subsidies of the Corpus Linguistics. Its general goal was to investigate the occurrence of nasality, in the dialect of these quilombola communities, and their linguistic behavior, considering the linguistic factors that can interfere in the phenomenon. Specifically it was aimed to a) detect the occurrence of nasalized vowels with the help of the resources that the Corpus Linguistics provides (Praat and WorldSmith Tolls); b) discriminate the different types of occurring contexts of nasalized vowels; c) make quantitative and qualitative analyzes of the nasalized vowels in the study corpus; d) describe and analyze the behavior of nasalized vowels and; e) contrast the values of F1 and F2 of the oral and nasalized vowels. It was hypothesized that the nasality happens because it is conditioned by the nasal segment following the nasalized vowel - phonological process of “assimilation” - its position as the primary stress and grammatical category. It was believed that the quilombolas communities of Brejo dos Crioulos and Poções produce nasalized vowels in their speech and this linguistic phenomenon is favored by the adjacent presence of consonants or nasal vowels. Furthermore, it was hypothesized that the values of F1 and F2 of oral and nasalized vowels in these communities are distinct. The following research questions were elaborated: (i) is the presence of nasalized vowels in the speech of these quilombola communities conditioned to the presence of a nasal sound segment? (ii) does the nasal sound segment following the nasalized vowel favor the occurrence of the nasality phenomenon? is there a difference between the values of F1 and F2 of the oral and nasalized vowels in both quilombola communities considered? To compose our corpus, 24 interviews recordings were used (12 female speakers and 12 male speakers), a total of 24 participants. It was found that the following nasal sound segment tends to condition the nasalized vowel. In general, it assimilates the lowering of the soft palate of nasal consonant segment immediately following, but there are cases of nasal vowel segment - regressive assimilation; the stressed syllable tends to favor the nasality, but it occurs in pretonic and postonic position as well; F1 and F2 values of oral and nasalized vowels in the quilombola communities of Poções and Brejo dos Crioulos are distinct: the group of Brejo dos Crioulos tends to produce the F1 of oral and nasalized vowels more lowered than the group of Poções and the F2, in a more anterior position. The nasality tends to occur in verbs and nouns, although it is not specific to a grammatical category. This research found cases of spurious nasalization, confirming previous studies. In turn, it revealed cases of lexical items with favorable context for nasalization, but with its non-occurrence. This last case, considered as the lowering of the uniform soft palate in PB, presented pronounced vowels without the soft palate lowering. That is, it was detected variation in the phenomenon of nasalization in PB. With this work, it was promoted the discussion about nasality, in order to contribute to the linguistic studies about the functioning of Brazilian Portuguese in this geographical context.